A extensão dos efeitos da cláusula compromissória a partes não-signatárias - Bahia, Maria Rita Dutra (2019)
This master's thesis is a comparative law study based on Portuguese and Brazilian jurisdictions and, consequently, it has the purpose of serving as an instrument to make the commercial arbitration legal system more coherent. In this paper, we will try to understand how the doctrine and case law of both jurisdictions have been applying the Group of Companies Doctrine in order to extend or not the effects of the arbitration clause to nonsignatory parties. Assuming that the development of the economy and commercial relations necessarily affect the interpretation and application of law, we will try to demonstrate that, nowadays, there is no more space for extremely conservative thoughts that do not meet the real intention of adopting arbitration as an alternative dispute resolution method, which is to make the legal system faster, safer and more effective. In addition, we will attempt to demonstrate that the restrictive interpretation of arbitration law based on the premise that the choice of arbitration is a waiver of the right of access to justice must, as soon as possible, be overcome. It is time to understand that arbitration is also an instrument of promotion of rights and access to justice.